2019
DOI: 10.3390/lubricants7020018
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz Time Domain Spectroscopy to Detect Different Oxidation Levels of Diesel Engine Oil

Abstract: Diesel engine oil was subjected to thermal oxidization (TO) for six periods of time (0 h, 24 h, 48 h, 72 h, 96 h, and 120 h) and was subsequently characterized by terahertz time domain spectroscopy (THz-TDS). The THz refractive index generally increased with oxidation time. The measurement method illustrated the potential of THz-TDS when a fixed setup with a single cuvette is used. A future miniaturized setup installed in an engine would be an example of a fixed setup. For the refractive index, there were high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Employing THz sensing to detect oxidation products—carbonyl and hydroxyl compounds—in oils is an effective technique, because those compounds are strongly polar and therefore strongly THz absorbing, allowing detection at low concentrations. A number of studies have been performed demonstrating high sensitivity and good discrimination of such measurements (Figure 22) [159,160,161,162,163,164,165]. Contamination by water can also be a cause of oil degradation, especially in engine oils where water is a product of fuel burning, and where sensitive THz detection has been demonstrated [165,166].…”
Section: Petrochemicalsmentioning
confidence: 99%
“…Employing THz sensing to detect oxidation products—carbonyl and hydroxyl compounds—in oils is an effective technique, because those compounds are strongly polar and therefore strongly THz absorbing, allowing detection at low concentrations. A number of studies have been performed demonstrating high sensitivity and good discrimination of such measurements (Figure 22) [159,160,161,162,163,164,165]. Contamination by water can also be a cause of oil degradation, especially in engine oils where water is a product of fuel burning, and where sensitive THz detection has been demonstrated [165,166].…”
Section: Petrochemicalsmentioning
confidence: 99%
“…Engine oil oxidation causes increased acidity, viscosity, gums, and sludge formation, and the depletion of chemical additives during service leads to engine oil deterioration [3]. Additives contribute to the resistance to oxidative stress that produces increased engine oil acidity, and oxidation occurs due to the interaction of air with oil [4] and contaminants such as glycol that react with engine oil and oxidize engine oil [5,6]. However, using petroleum-derived oil base and refining additives in lubricants is linked to adverse effects on human health and the environment [7].…”
Section: Introductionmentioning
confidence: 99%
“…22 The Terahertz Time Domain Spectroscopy method demonstrated an oxidation time measurement. 23 Previous research showed the possibility of using colour features to analyse particles for automated wear debris classification. 24 Published literature shows the use of an optical colour sensor with a blue LED as a light source and light-dependent resistor by infrared sensor setup 1 (LDR) or colour scale as per the ASTM D1500 standard for colour analysis.…”
Section: Introductionmentioning
confidence: 99%